A case study on stress management among employees of Maybank at Jerantut, Mentakab and Temerloh Pahang / Siti Azwani Abdullah - Abdullah, Siti Azwani (2013)
Stress is a common feeling or emotion that everyone will be faced. The purpose of this study is to explore how employee managed his or her work related stress specifically in banking sector. The scope of this study is all the staff at Maybank in Jerantut, Mentakab and Temerloh. The descriptive study used a random sampling technique. The methodology used in this study was questionnaires. The data collected was analyzed using the Statistical Package for Social Science (SPSS, Version 20.0). Random sampling has been used to conduct this research where a sample random is applied to choose the respondents. The major findings for this research are the main stressor affecting employee's performance, impact of stress on employee well-being, the way staffs cope with their stress and the program that organization was provided for their staff to manage stress. Thus, finding was found that Maybank have their own initiative in order to prevent their staff from stress such as providing training. The training was conducted by the academy itself. This study highlighted several recommendations in order to continuously improve their productivity. Maybank must upgraded their training for the staff. Indirectly, it will increase their productivity and the image of Maybank will be recognized and equitable around the world.